1968
DOI: 10.1029/ja073i001p00001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric properties deduced from OGO 1 observations of ducted and nonducted whistlers

Abstract: The OGO 1 satellite has yielded evidence for both ducted and nonducted modes of whistler propagation in the magnetosphere. Two new types of nonducted whistlers have been identified: the ‘magnetospherically reflected’ whistler and the ‘Nu’ whistler. These whistlers have never been observed on the ground. Their unique properties result in part from the presence of ions that permit reflection of whistler‐mode energy in the magnetosphere. These phenomena provide a new tool for study of the distribution of ionizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
121
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(127 citation statements)
references
References 16 publications
6
121
0
Order By: Relevance
“…An unexpected possibility for whistler-wave reflection when the ions are taken into account in the dispersion relation, and the visualisation of this effect by ray tracing, were first demonstrated by Kimura (1966). In a sense, this finding predicted magnetospherically reflected (MR) whistlers, which were found in the spectrograms of wave data from OGO 1 and 3 (Smith and Angerami, 1968). In their study, mainly devoted to MR whistlers, Smith and Angerami also pointed out that the spectrogram of an MR whistler observed far from the equator may have the shape of the Greek letter ν.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…An unexpected possibility for whistler-wave reflection when the ions are taken into account in the dispersion relation, and the visualisation of this effect by ray tracing, were first demonstrated by Kimura (1966). In a sense, this finding predicted magnetospherically reflected (MR) whistlers, which were found in the spectrograms of wave data from OGO 1 and 3 (Smith and Angerami, 1968). In their study, mainly devoted to MR whistlers, Smith and Angerami also pointed out that the spectrogram of an MR whistler observed far from the equator may have the shape of the Greek letter ν.…”
Section: Introductionmentioning
confidence: 84%
“…The main focus of the present study is Nu whistlers, which were first reported by Smith and Angerami (1968). We have presented many examples of Nu whistlers from MA-GION 5 measurements, using numerical simulations as a tool for understanding their main features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After an initial rapid rise in frequency, these waves asymptotically approach the proton cyclotron frequency. Smith and Angerami (1968), using measurements on OGO 1 and OGO 3 satellites, first reported Magnetospherically Reflected (MR) whistlers predicted by Kimura (1966). The MR whistlers are highly oblique (with respect to magnetic field lines) propagating waves that undergo a reflection in the region where their frequency is close to the local Lower Hybrid Resonance (LHR) frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Lightning-generated whistlers were detected by the plasma wave instrument on Voyager I in three distinct The dispersion of whistlers was initially used as a remote probe for plasma properties in the Earth's inner magnetosphere [Helliwell, 1965;Smith and Angerami, 1968]. Subsequently, the dispersion of Jovian whistlers was analyzed to estimate the electron and light ion (H +) densities along field-aligned propagation paths between the Jovian ionosphere and the Io torus [Tokar et al, 1982a, b].…”
Section: Introductionmentioning
confidence: 99%